DISKRIMINASI GENDER PADA PENARI LENGGER LANANG BANYUMAS - Nurcholis Aprian (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2022)
Lengger Lanang is a Banyumas folk art that has recently been revived and has beenwelcomed by the local population. The man is dressed like a woman and dancesaccompanied by Gamelan or Karon. This typical Banyumas dance is performed bymen who totally transform into women when performing the dance. Some of thedancers are still male, live like men, and even have children and wives. However,there are also transgender people. This study uses qualitative research methods withdata collection techniques used in this study are observation, interviews anddocumentation and literature used as a study to reinforce the results of interviews.The data validity technique used source tringulation. The result of this research isthat there is discrimination experienced by lengger lanang dancers because they areconsidered as transgender or LGBT people and are considered as an association thatcarries out forbidden movements that use make-up and clothing like women whenperforming. The view that men must appear to bring out their masculinity willinfluence the successor's interest in the lengger lanang dance.